Some studies on Sudanese sheep. I. Preliminary observations on early weight changes in lambs under Gezira conditions - El-Amin, F.M. (1975)
The experiment was designed to study birth weight, weaning weight, 18 weeks body weight and 22 weeks body weight of lambs born in El-Huda Sheep Improvement Station. There were differences between male and female lambs for all the ages studied. There was a marked seasonal effect on birth weight. Lambs born in December were heavier than those born in November. Mortality was relatively high with most of the losses occurring in the preweaning period. Males had higher mortality than females.